Hard goals : the secrets to getting from where you are to where you want to be - Murphy, Mark A. (Mark Andrew) (McGraw Hill-Ascent Audio, 2010)
"Ever felt like you weren't reaching your goals as fast as you would like? HARD GoalsK shows you how to change your thinking and get on the path to tremendous achievement!"--Marshall Goldsmith, world-renowned executive coach and author of the New York Times bestsellers MOJO and What Got You Here Won't Get You There "Hard Goals is full of fascinating insights regarding how to get yourself to achieve things you never thought possible, and Murphy's key ideas have strong research support. ... If you want to achieve something great or important in your life, this is the book for you." -Edwin A. Locke, Ph. D., Professor Emeritus, University of Maryland "If you want a mediocre life, set ho-hum goals. If you want a life filled with excellence and meaning, set HARD Goals. This book shows you how to set HARD Goals and love every minute of achieving them. The end result? Winning in life and unparalleled fulfillment." Lyle Nelson, four-time Olympian and author of Spirit of Champions "Every company has goals these days. So why do most goals fall short? Why do leaders keep setting the same failed goals year after year? HARD Goals gives you the cutting-edge science to engage every employee in pursuing and achieving extraordinary goals. No more procrastination, foot-dragging, or giving up. With HARD Goals, your organization will achieve astonishing results. Every CEO, manager, and employee needs to read this book!" Kevin M. Andrews, President, SmartBen Want to increase sales? Get promoted? Change the world? There's a goal for that ... Steve Jobs, Jeff Bezos, the school teacher next door who amassed a million-dollar fortune ... Did these people succeed because they were more motivated or because they were more disciplined? The answer to both questions is yes-but not in the ways you might think. Anyone can achieve extraordinary things. The secret is setting goals that test the very limits of your abilities. In Hard Goals, Mark Murphy, the acclaimed author of Hundred Percenters, explains the science behind getting from where you are to where you want to be in your career, business, and life. Leadership IQ, Murphy's top-rated leadership training consultancy, studied nearly 5,000 workers from virtually every field and found that extraordinary goals-the kind that got America to the moon and back, developed the iPod, created nanotechnology, and helped individuals overcome tremendous personal adversity-stimulate and engage the brain in ways that are profoundly different from the goals most people set. Research conducted for this book revealed that people who set Hard goals are up to 75 percent more fulfilled than people with easy goals. In these pages, Mark Murphy explains how success, and the satisfaction it brings, comes from knowing how to set goals that are: Heartfelt-have an emotional attachment, "scratch an existential itch." Animated-motivated by a vision, that movie that plays over and over in your mind. Required-imbued with such a sense of urgency that you have no other choice but to start acting on them right here, right now. Difficult-the greatest achievements come from the toughest challenges-but they also leave you feeling stronger, smarter, and more fulfilled. People set goals all the time, but the majority end up unfulfilled or abandoned. With all the challenges facing us today, we could use a little more achievement. Hard Goals can help us get there by offering the hard science and practical techniques to conquer procrastination and unlock your brain's potential for realizing your goals